Issues and problems of the brassware handicraft industry in Terengganu, Malaysia - Ahmad Mohamad, Sharih; Norzaman, Nor Ziratul Aqma; Mohamed Yusof, Shahrul Anuwar; Abd. Rahman, Khairul Aidil Azlin; Abdullah, Muhammad Firdaus Abong; Md. Zulkifli, Addy Putra; Razali, Amirul Fahmi (Malay Arts, Culture and Civilization Research Centre, Institute of the Malay World and Civilization, 2023)
Terengganu has a historical record of being a formidable old commerce hub, renowned for its local wisdom and its residents' expertise in handicrafts, particularly in the creation of brassware handicraft. The brassware handicraft sector is less popular than other handicrafts like songket, batik, wood carving, weaving, etc. Additionally, its production rate has been decreasing. Therefore, the study aims to identify issues and problems that contribute to the decline of the brassware handicraft industry in Terengganu. This study primarily employs qualitative research methods, which encompass external inquiries such as semi-structured interviews and the thorough literature reviews and interpretation of collected data. The SPSS Text Analytics for Surveys software is utilised to analyse data obtained from interviews with 28 respondents directly involved in the brassware craft business. The investigation yielded a validation model demonstrating the association between the various concerns and problems in the brassware handicraft sector in Terengganu. Based on the findings of this study, the researcher has categorised the challenges and concerns that need to be considered by those interested in developing brassware crafting in Terengganu in the future. These problems are typically categorised into three tiers: individual level, collective level, and national level. A clear understanding of the issues and problems among stakeholders through the validation model produced can increase the value of heritage handicrafts in Terengganu and guarantee the sustainability of local wisdom so that it is preserved and not lost over time.